Expression and significance of the Hedgehog signal transduction pathway in oxygen-induced retinal neovascularization in mice - Liu ML; Chen XL; Liu HN; Di Y (Dove Medical Press, 2018)
Meilin Liu, Xiaolong Chen, Henan Liu, Yu Di Department of Ophthalmology, Shengjing Affiliated Hospital, China Medical University, Shenyang, Liaoning, People’s Republic of China Aim: The aim of the study was to investigate the signal transduction mechanism of Hedgehog–vascular endothelial growth factor in oxygen-induced retinopathy (OIR) and the effects of cyclopamine on OIR. Methods: An OIR model was established in C57BL/6J mice exposed to hyperoxia. Two hundred mice were randomly divided into a control group, an OIR group, an OIR-control group (treated with isometric phosphate-buffered saline by intravitreal injection), and a cyclopamine group (treated with cyclopamine by intravitreal injection), with 50 mice in each group. The retinal vascular morphology was observed using adenosine diphosphatase and number counting using hematoxylin and eosin-stained image. Quantitative real-time quantitative polymerase chain reaction was used to detect mRNA expression. Protein location and expression were evaluated using immunohistochemistry and Western blot. Results: The OIR group and OIR-control group demonstrated large-area pathological neovascularization and nonperfused area when compared with the control group (both P<0.05). The area of nonperfusion and neovascularization in the cyclopamine group was significantly reduced compared with the OIR and OIR-control groups (both P<0.05). Compared with the control group, the OIR and OIR-control groups had more vascular endothelial cells breaking through the inner limiting membrane. The number of new blood vessel endothelial cell nuclei in the cyclopamine group was significantly reduced (both P<0.05) when compared with the OIR and OIR-control groups. The mRNA and protein expressions of Smoothened, Gli1, and vascular endothelial growth factor in the signal pathway of the OIR and OIR-control groups were significantly higher than those of the control group; however, in the cyclopamine group, these factors were reduced when compared with the OIR and OIR-control groups (all P<0.05). Conclusion: Our data suggest that abnormal expression of the Hedgehog signaling pathway may be closely associated with the formation of OIR. Inhibiting the Smoothened receptor using cyclopamine could control retinal neovascularization, providing new ideas and measures for the prevention of oxygen-induced retinal neovascularization. Keywords: Hedgehog signaling pathway, neovascularization, oxygen-induced retinopathy, retinopathy of prematurity, cyclopamine